An inverse heat transfer method for determination of the workpiece temperature in grinding - Gostimirović, Marin; Kovač, Pavel; Sekulić, Milenko; Savković, Borislav (Journal of Production Engineering, 2009)
This paper present investigation of the thermal state in grinding process, using inverse heat transfer problems. Based on a temperature measured at any point within a workpiece, this experimental and analytical method allows determination of the maximal temperature on wheel/workpiece interface as well as the complete temperature field in the workpiece surface layer. To solve the inverse heat transfer problems, a numerical method of finite differences in implicit form was chosen.